2019
DOI: 10.1029/2019gl083123
|View full text |Cite
|
Sign up to set email alerts
|

How Did South China Connect to and Separate From Gondwana? New Paleomagnetic Constraints From the Middle Devonian Red Beds in South China

Abstract: The paleogeographic relationship between South China and Gondwana is critical for understanding the dispersion of Gondwana, accretion of Asia, and evolution of the Paleo‐Tethys. However, the lack of robust Devonian paleomagnetic data prevents a confirmative reconstruction of South China's connection to Gondwana and its subsequent separation during the Paleozoic. Here we report a new paleopole (33.6°N, 236.4°E; A95 = 3°) from the Givetian red beds (~385 Ma) in central South China. Fitting apparent polar wander … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…As illustrated in Figure 6, a comprehensive rifting history of South China‐Indochina form Gondwana during the Devonian to Early Permian is shown. The separation of South China‐Indochina from eastern Gondwana (Figures 6a and 6b) is revised from Xian et al (2019) and Torsvik and Cocks (2017). The new paleomagnetic data in this study, combining with previous reported (Yan et al, 2019; Zhang et al, 2015, and references therein), indicate that the middle Carboniferous to Early Permian (Figures 6c and 6d) period is a tectonically quiet interval for the North Qiangtang‐Indochina‐South China blocks, because no significant drift occurred, which is also shown with paleolatitude variations in Figure 7.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As illustrated in Figure 6, a comprehensive rifting history of South China‐Indochina form Gondwana during the Devonian to Early Permian is shown. The separation of South China‐Indochina from eastern Gondwana (Figures 6a and 6b) is revised from Xian et al (2019) and Torsvik and Cocks (2017). The new paleomagnetic data in this study, combining with previous reported (Yan et al, 2019; Zhang et al, 2015, and references therein), indicate that the middle Carboniferous to Early Permian (Figures 6c and 6d) period is a tectonically quiet interval for the North Qiangtang‐Indochina‐South China blocks, because no significant drift occurred, which is also shown with paleolatitude variations in Figure 7.…”
Section: Discussionmentioning
confidence: 94%
“…The initial occurrence of pelagic radiolarian cherts and ophiolites in the Paleo‐Tethys suture zone suggest that the separation of South China‐Indochina‐North Qiangtang from Gondwana occurred since the Early‐Middle Devonian (Li et al, 1995, 2016; Metcalfe, 2013; Zhong, 1998). This interpretation is supported paleomagnetically through fitting apparent polar wander paths which indicated the rifting of South China‐Indochina from Gondwana occurred during ~400–385 Ma (Xian et al, 2019). Considering the Permian‐Triassic drifting history of the North Qiangtang and Indochina blocks has been schematically described (Ma et al, 2019; Song et al, 2017; Yan et al, 2018, 2019), reconstructing the Carboniferous configuration of eastern Gondwana blocks is essential to depict the evolution of the Paleo‐Tethys Ocean and provides clues for understanding the geodynamic mechanism of the dispersion.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations